2010
DOI: 10.1007/s00425-010-1151-8
|View full text |Cite
|
Sign up to set email alerts
|

The SUMO conjugation pathway in Populus: genomic analysis, tissue-specific and inducible SUMOylation and in vitro de-SUMOylation

Abstract: Covalent attachment of the small ubiquitin-like modifier (SUMO) to proteins in eukaryotic cells can regulate an assortment of cellular processes including transcription, and DNA-protein and protein-protein interactions. We identified gene models and found evidence for expression of genes involved in SUMOylation and SUMO deconjugation in Populus. We detected SUMOylated proteins in diverse organ and tissue types. SUMOylation was altered during responses to heat shock, desiccation, peroxide and irrigation of root… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…At the same time, the level of free SUMO was greatly reduced from 1 h of treatment, and when treated for 24 h, most free SUMOs have been exhausted in soybean roots. Consistent with the results got from poplar (Reed et al, 2010 ), SUMOylation by salinity treatment in soybean roots was rapidly inducible and probably has some functional implications.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…At the same time, the level of free SUMO was greatly reduced from 1 h of treatment, and when treated for 24 h, most free SUMOs have been exhausted in soybean roots. Consistent with the results got from poplar (Reed et al, 2010 ), SUMOylation by salinity treatment in soybean roots was rapidly inducible and probably has some functional implications.…”
Section: Resultssupporting
confidence: 89%
“…SUMO conjugation was reported to be essential in Arabidopsis , and an increasing number of papers have demonstrated that mutants that were not able to attach SUMO1/2 onto substrate proteins exhibit typical phenotypes such as growth reduction, impaired salinity, drought, heat and freezing tolerance, and altered response to phosphate starvation (Roden et al, 2004 ; Catala et al, 2007 ; Miura et al, 2007b , 2011 ; van den Burg et al, 2010 ). Previous studies with rice ( Oryza sativa ) and poplar ( Populus strichocarpa ) showed that SUMOylation can be significantly enhanced upon heat, cold, high salinity, and abscisic acid exposure (Chaikam and Karlson, 2010 ; Reed et al, 2010 ; Li et al, 2013 ), which was always accompanied by a decrease in the pool of free SUMO and correlated with the duration and intensity of the stress. Interestingly, SUMOylation levels decrease within hours or even minutes when the heat shocked plants returned to the normal temperature, suggesting that SUMOylation acts transiently and reversibly (Kurepa et al, 2003 ; van den Burg et al, 2010 ).…”
Section: Introductionmentioning
confidence: 97%
“…In plants, proteomic and mass spectrometric analyses identified a large number of SUMO substrates implicated in a wide array of biological pathways, implying important roles sumoylation may play in the regulation of diverse plant processes (Elrouby and Coupland, ; Miller and Vierstra, ; Miller et al ., ; Park et al ., ). Indeed, numerous studies in Arabidopsis and other plant species have established biological functions of different components of SUMO conjugation system in various aspects of plant development and stress responses (Park et al ., ; Reed et al ., ). For example, genetic analysis of SUMO conjugation mutants and transgenic (TG) studies in Arabidopsis revealed that sumoylation is essential for viability.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, heat-induced SUMO conjugates were detected in the nuclear fraction, suggesting that sumoylation is involved in the signaling and early response to heat stress (Saracco et al, 2007). In addition to Arabidopsis and tomato, SUMO gene families are present in other plants such as poplar, grape, sorghum, and rice (Kurepa et al, 2003;Reed et al, 2010;van den Burg et al, 2010). AtSUM1 is expressed from the early embryo stages (globule, heart, and torpedo stage) and its expression is constitutive in most organs (especially in the leaf and root), except for the vasculature, lateral root primordia and the root apex where AtSUM2 is highly expressed.…”
Section: Small Ubiquitin Like Modifier (Sumo)mentioning
confidence: 99%